Implikasi Yuridis Dianutnya Causal Stelsel Terhadap Kekuatan Mengikat Sertifikat Tanah Objek Hak Tanggungan - Tunggu, Rafael (LPPM Universitas Ekasakti Padang, 2023)
This research was conducted to determine and analyze the juridical implications of adopting causal stelsel on the binding strength of land certificates obtained from the auction results for the execution of mortgage rights. The legal problem is how the juridical implications of adopting causal stelsel have on the binding force of land certificates obtained from auction results for the execution of mortgage rights. To achieve the research objectives, a document study of the Makassar District Court Decision Number: 278/Pdt.G/2018/PN-Mks has been carried out using three approaches, namely the conceptual approach, legislation and legal objectives. The results of the research show that in his legal considerations the judge stated that the land certificate obtained from the auction for the execution of mortgage rights does not have binding force if it can be proven that from a historical perspective the certificate was issued for the first time on the basis of an unlawful act, namely the party who sold the land for the first time had no right. act freely on the object of buying and selling. As a result, auction buyers who are not aware of hidden defects in the auction object do not receive legal protection.